Volunteer works of university Lecturers: Case of Thammasat University - มงกุฎวิสุทธิ์, ศรีสุข (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2018)
Volunteer works of university Lecturers: case of Thammasat University were the study of opinion on activities and volunteering project of university’s faculty members. 56 lecturers. From all participants, and most female were single and most of them were at the age of 36-40 years old and volunteering activities were having 5-10 years of work experiences. Their opinion towards the benefits of participating in volunteering activities was that it allows the faculty members to be good model for students and other people in the university. Furthermore, it also provides opportunity to see what were really happening in the society, It was a good way to develop volunteer spirit and create networks. The forms of volunteering activities consultants, lecturers or speakers on what they are good at. They have defined volunteering activities as volunteering and willing to do with the intrinsic desire not an additional duty after work to help others, help society, and create benefit to the society”. It is educational services help disseminate knowledge, sacrifice, energy, brain, other stuffs etc. This helps creating value, reducing self-identity, and developing public mind towards the society. Recommendations that support faculty members in participating in volunteering activities include the development of network of faculty members who have public mind in order to create space for exchanging information about volunteering project. In addition, university should support and make benefit from faculty members who have public mind. It was not only a good model for students, but also makes use of willingness in doing good thing to develop the university.